Triggers of Nonfatal Myocardial Infarction in Costa Rica: Heavy Physical Exertion, Sexual Activity, and Infection - Baylin, Ana (2007)
Purpose There are no data for factors that could trigger myocardial infarction (MI) in the context of lifestyles in developing countries. Methods Using a case–crossover design, we assessed the effect of heavy physical exertion, sexual activity, acute respiratory tract infections, and gastroenteritis as triggers for MI in 530 survivors of a first MI from Costa Rica. Results Relative risks (RRs) for MI in the hour after heavy physical exertion and 2 hours after sexual activity were 4.94 (95% confidence interval [CI], 3.73–6.54) and 5.47 (95% CI, 2.71–11.02). Risk for MI after heavy physical exertion was greater for patients with poor physical fitness or elevated underlying cardiovascular risk (p < 0.0001 and p = 0.06, tests of homogeneity). RRs for acute respiratory tract infection and gastroenteritis were 1.48 (95% CI, 0.92–2.38) and 1.27 (95% CI, 0.95–1.69), respectively. Patients with three or more risk factors had an RR for MI for gastroenteritis of 2.08 (95% CI, 1.31–3.28). Conclusions Our results confirm previous studies in developed countries showing that heavy physical exertion and sexual activity are potential triggers for MI, and their effect is modified by physical fitness and underlying cardiovascular risk. Additional studies that explore the biologic effects of gastroenteritis as triggers of MI are warranted.